Legal status of the pharmacy practice in the European Union and the Republic of Macedonia - J. Patcheva; K. Mladenovska; L. Petrusevska Tozi (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2012)
From a historical point of view, one can notice that the role of the pharmacists employed in community and hospital pharmacies became more complex. Today, they do not only supply, store, prepare and dispense medicines with ensured quality, but they also provide professional services based on the concept of pharmaceutical care and good pharmacy practice. In this paper, detailed review on the current legislative regulating the status and practice of the community and hospital pharmacies in some EU-member countries and in Macedonia is given. The implementation of the concept of pharmaceutical care and good pharmacy practice in selected EU member-countries, Great Britain, Germany and Slovenia, and in Croatia as a future EU member as well as in Macedonia is also discussed. In addition, set of recommendations for establishing the good pharmacy practice standards is prepared and presented. At the end, an attempt is made to establish a basis for development a modern Law on Pharmacy Practice in the Republic of Macedonia.